2003
DOI: 10.1073/pnas.1432836100
|View full text |Cite
|
Sign up to set email alerts
|

A large pool of releasable vesicles in a cortical glutamatergic synapse

Abstract: To probe exocytosis at a cortical glutamatergic synapse, we made capacitance measurements in whole-cell recorded hippocampal mossy fiber terminals. Evaluation of different methods by using a morphology-based equivalent electrical model revealed that quantitative capacitance measurements are possible in this presynaptic structure. Voltage pulses leading to presynaptic Ca 2؉ inflow evoked large capacitance signals that showed saturation with increasing pulse duration. The mean peak capacitance increase was 100 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
215
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(245 citation statements)
references
References 59 publications
23
215
7
Order By: Relevance
“…The rise time of the Ca 2ϩ tail currents, which are almost instantaneous, indicates that the Ca 2ϩ channels are located in mossy fiber terminals rather than adjacent axons. For the MFB, this means that the speed of voltage clamp is limited by the kinetics of the charging of the bouton, which occurs with a time constant ϭ R s ϫ C MFB Ϸ 15 M⍀ ϫ 2 pF ϭ 30 s, where R s is the uncompensated series resistance and C MFB is the bouton capacitance (Geiger and Jonas, 2000;Hallermann et al, 2003) (see Materials and Methods). Thus, direct recording from hippocampal MFBs allows us to study the gating of identified Ca 2ϩ channel subtypes with unique temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The rise time of the Ca 2ϩ tail currents, which are almost instantaneous, indicates that the Ca 2ϩ channels are located in mossy fiber terminals rather than adjacent axons. For the MFB, this means that the speed of voltage clamp is limited by the kinetics of the charging of the bouton, which occurs with a time constant ϭ R s ϫ C MFB Ϸ 15 M⍀ ϫ 2 pF ϭ 30 s, where R s is the uncompensated series resistance and C MFB is the bouton capacitance (Geiger and Jonas, 2000;Hallermann et al, 2003) (see Materials and Methods). Thus, direct recording from hippocampal MFBs allows us to study the gating of identified Ca 2ϩ channel subtypes with unique temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of PNAS, Hallermann et al (1) present capacitance measurements from hippocampal mossy fiber nerve terminals during stimulated exocytosis. These are the first time-resolved membrane capacitance measurements from bona fide (albeit relatively large) bouton-type synaptic terminals, with diameters of Ϸ3 m and a resting capacitance of Ϸ1 pF.…”
mentioning
confidence: 99%
“…However, a rigorous modeling of such capacitance measurements would be useful to show the theoretical relationship of measured to true changes in membrane capacitance for different-length axons. The approach adopted by Hallermann et al (1) to calculate membrane capacitance from currents recorded from the mossy fiber terminal in slice started with an anatomical model obtained by reconstruction of a biocytin-filled terminal. Although they record directly from the bouton (where the active zones are located and thus the putative site of exocytotic capacitance changes), the presence of multiple large associated processes makes direct application of the spherical cell approximation inadequate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those results supported the hypothesis that one of the mechanisms triggered by LTP at mossy fiber is the organization or activation of, at least, the presynaptic machinery responsible for the efficient stimulus-secretion coupling and neurotransmitter release at previously presynaptically silent or 'mute' synapses. 38,40,41 Although a recent study has reported direct measurements of synaptic vesicle exocytosis from single mossy fiber terminals by means of membrane capacitance measurements, 42 most of the studies performed to analyze the synaptic plasticity mechanisms at mossy fibers are based on electrophysiological analysis of the simultaneous activity of multiple synapses. The postsynaptic terminals contacted by mossy fibers are complex dendritic spines known as thorny excrescences, 43 which are interdigitated with protrusions of the mossy fiber terminals, presenting discrete postsynaptic densities apposed to multiple (up to [30][31][32][33][34][35] presynaptic release sites (reviewed in Henze et al 44 ), which normally present multiquantal release.…”
Section: Presynaptic Ltp Independent Of Nmda Receptormentioning
confidence: 99%